Tanggung Jawab Penyelenggara Jasa Marketplace Terhadap Perdagangan Software Bajakan berdasarkan PP No. 80 Tahun 2019 Tentang Penyelenggaraan Transaksi Melalui Sistem Elektronik - Muhamad Firhan Fauzan; Neni Sri Imaniyati (UNISBA Press, 2022)
Abstract. Software or computer program is an object of creation that is protected by the copyright regime based on Article 40 Paragraph 1 letter (s) of Law Number 28 of 2014 concerning Copyright. Software that can be purchased legally will get an official license as a sign of the legality of ownership of the software, however, trade in pirated software is rife in the online marketplace buying and selling platforms. The problems that will arise are 1.) What are the Responsibilities of Marketplace Service Providers Against Pirated Software Trading According to Regulations Legislation ? 2.) What are the Legal Consequences of the Implementation of the Marketplace on the Trading of Pirated Software Based on Government Regulation No. 80 of 2019 concerning the Implementation of Transactions Through Electronic Systems? The method used is qualitative normative with a normative juridical approach by using secondary data in the form of primary legal materials (laws and regulations) and secondary legal materials from the literature (doctrine, journals, internet, books) relating to rights. Intellectual Property according to Law Number 28 of 2014 concerning Copyright and Government Regulation No. 80 of 2019 concerning the Implementation of Transactions Through Electronic Systems. Based on the results of research and discussion, it can be concluded that Shopee's responsibility for trading pirated software on the marketplace platform it manages is included in the scope of several laws and regulations, namely Government Regulation Number 80 of 2019 concerning Trading Through Electronic Systems, then Law Number 11 of 2019 2008 concerning Information and Electronic Transactions and Law Number 28 of 2014 concerning Copyright. Legal actions between the seller and Shopee, both of which are part of the marketspace platform, have legal consequences, namely the loss of the economic rights of the copyright holder 10 and 114 UUHC can be a legal basis to impose responsibility on the organizers of the Shopee marketplace Keywords: Software, marketplace, responsibility. Abstrak. Software atau program komputer merupakan objek ciptaan yang dilindungi oleh rezim hak cipta berdasarkan Pasal 40 Ayat 1 huruf (s) Undang-undang Nomor 28 Tahun 2014 tentang Hak Cipta. Software dapat dibeli secara legal akan mendapatkan lisensi resmi sebagi tanda legalitas atas kepemilikan software tersebut namun, perdagangan software bajakan marak terjadi di platform jual beli online marketplace.Permasalahn yang akan muncul adalah 1.) Bagaimana Tanggung Jawab Penyelenggara Jasa Marketplace Terhadap Perdagangan Software Bajakan Menurut Peraturan Perundang-Undangan ? 2.)Bagaimana Akibat Hukum Dari Penyelenggaraan Marketplace Terhadap Perdagangan Software Bajakan Berdasarkan Peraturan Pemerintah No 80 Tahun 2019 Tentang Penyelenggaraan Transaksi Melalui Sistem Elektronik ? Metode yang digunakan yaitu normatif kualitatif dengan pendekatan yuridis normatif dengan dengan menggunakan data-data sekunder berupa bahan-bahan hukum primer (peraturan perundang-undangan) dan bahan-bahan hukum sekunder dari kepustakaan (doktrin, jurnal, internet, buku) yang berkaitan dengan Hak Kekayaan Intelektual menurut Undang-Undang Nomor 28 tahun 2014 tentang Hak Cipta serta Peraturan Pemerintah No 80 Tahun 2019 Tentang Penyelenggaraan Transaksi Melalui Sistem Elektronik. Berdasarkan hasil penelitian dan pembahasan dapat disimpulkan, Pertanggungjawaban pihak Shopee terhadap perdagangan software bajakan di platform marketplace yang dikelolanya termasuk kedalam lingkup dari beberapa peraturan perundang-undangan, yaitu Peraturan Pemerintah Nomor 80 Tahun 2019 Tentang Perdagangan Melalui Sistem Elektronik, Kemudian Undang-undang Nomor 11 Tahun 2008 Tentang Informasi Dan Transaksi Elektronik Serta Undang-undang Nomor 28 Tahun 2014 Tentang Hak Cipta. Perbuatan hukum antara pihak penjual dan pihak Shopee yang keduanya merupakan bagian dari platform marketpace menimbulkan akibat hukum yaitu hilangnya hak ekonomi pemegang hak cipta 10 dan 114 UUHC dapat menjadi dasar hukum untuk membebankan pertanggungjawaban kepada pihak penyelenggara marketplace Shopee. Kata Kunci: Software, marketplace, tanggung jawab.